PERTENTANGAN ID, EGO DAN SUPEREGO DALAM PEMBENTUKAN KARAKTER TOKOH EDMUND PADA FILM THE CHRONICLES OF NARNIA: THE WITCH, THE LION AND THE WARDROBE - Anggina Aritonang; Nungki Heriyati (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2022)
This study aims to analyze the characterization of Edmund in The Chronicles of Narnia: The Witch, The Lion and The Wardrobe film. As for in revealing the character of Edmund, the author will analyzed through psychoanalysis approach from Sigmund Freud about the Id, Ego and Superego. This approach is used ,because the theory of psychoanalysis is able to reveal the unconscious impulses that affect human behavior. Through such behavior, researchers can determine the portrayal of Edmund's character. Data collection was conducted with descriptive qualitative method. The result of this research is the contradiction between the id, ego and superego which is completely dominated by the id. The domination of the id affects the behavior of Edmund which is loving, curious, ambitious, impressionable, greedy, liar and courageous. Keywords: Film, Characterization, Psychoanalysis